Insect oviposition preference between Epichloe-symbiotic and Epichloe-free grasses does not necessarily reflect larval performance - Laihonen M; Saikkonen K; Helander M; Tammaru T (WILEY, 2022)
Variation in plant communities is likely to modulate the feeding and oviposition behavior of herbivorous insects, and plant-associated microbes are largely ignored in this context. Here, we take into account that insects feeding on grasses commonly encounter systemic and vertically transmitted (via seeds) fungal Epichloe endophytes, which are regarded as defensive grass mutualists. Defensive mutualism is primarily attributable to alkaloids of fungal origin. To study the effects of Epichloe on insect behavior and performance, we selected wild tall fescue (Festuca arundinacea) and red fescue (Festuca rubra) as grass-endophyte models. The plants used either harbored the systemic endophyte (E+) or were endophyte-free (E-). As a model herbivore, we selected the Coenonympha hero butterfly feeding on grasses as larvae. We examined both oviposition and feeding preferences of the herbivore as well as larval performance in relation to the presence of Epichloe endophytes in the plants. Our findings did not clearly support the female's oviposition preference to reflect the performance of her offspring. First, the preference responses depended greatly on the grass-endophyte symbiotum. In F. arundinacea, C. hero females preferred E+ individuals in oviposition-choice tests, whereas in F. rubra, the endophytes may decrease exploitation, as both C. hero adults and larvae preferred E- grasses. Second, the endophytes had no effect on larval performance. Overall, F. arundinacea was an inferior host for C. hero larvae. However, the attraction of C. hero females to E+ may not be maladaptive if these plants constitute a favorable oviposition substrate for reasons other than the plants' nutritional quality. For example, rougher surface of E+ plant may physically facilitate the attachment of eggs, or the plants offer greater protection from natural enemies. Our results highlight the importance of considering the preference of herbivorous insects in studies involving the endophyte-symbiotic grasses as host plants.